2023
DOI: 10.3390/app132011605
|View full text |Cite
|
Sign up to set email alerts
|

The Dose-Dependent Role of Sage, Clove, and Pine Essential Oils in Modulating Ruminal Fermentation and Biohydrogenation of Polyunsaturated Fatty Acids: A Promising Strategy to Reduce Methane Emissions and Enhance the Nutritional Profile of Ruminant Products

Mostafa Bokharaeian,
Taghi Ghoorchi,
Abdolhakim Toghdory
et al.

Abstract: The livestock industry significantly contributes to greenhouse gas emissions, with ruminant animals, including cows, sheep, and goats, being responsible for a substantial share of these emissions due to methane production. Reducing methane emissions from ruminants is crucial for mitigating the environmental impact of livestock production. Additionally, there has been a growing interest in improving the nutritional quality of ruminant products through modifying their profile of fatty acids. The current study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
(77 reference statements)
2
2
2
Order By: Relevance
“…This supports the fact that a lower pH is related to a higher total SCFA concentration [ 45 ]. A higher pH with higher doses of sage essential oil was reported by Bokharaeian et al [ 18 ], which agrees with the findings of this study. The molar concentration of acetate changed linearly and quadratically and that of the propionate changed quadratically, with the highest concentration of both SCFAs shown at 1% inclusion of SO and then decreased with higher inclusion.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This supports the fact that a lower pH is related to a higher total SCFA concentration [ 45 ]. A higher pH with higher doses of sage essential oil was reported by Bokharaeian et al [ 18 ], which agrees with the findings of this study. The molar concentration of acetate changed linearly and quadratically and that of the propionate changed quadratically, with the highest concentration of both SCFAs shown at 1% inclusion of SO and then decreased with higher inclusion.…”
Section: Discussionsupporting
confidence: 93%
“…It was expected that the inclusion of SO would show anti-methanogenic activity by improving substrate degradability and the ruminal fermentation profile, and inhibiting methanogenic archaea, thereby decreasing CH 4 production. The production of CH 4 decreased linearly in the current study, which is concurrent with the findings of others in which dried leaves and sage essential oil were evaluated in vitro [ 9 , 10 , 18 , 38 ]. Patra and Saxena [ 39 ] demonstrated that essential oils, organosulfur compounds, and flavonoids can impact CH 4 production through the direct inhibition of methanogens without altering the population of protozoa.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations